A single molecule investigation of i-motif stability, folding intermediates, and potential as in-situ pH sensor - Mustafa, Golam; Gyawali, Prabesh; Taylor, Jacob A.; Maleki, Parastoo; Nunez, Marlon V.; Guntrum, Michael C.; Shiekh, Sajad; Balci, Hamza (Frontiers in Molecular Biosciences, 2022)
We present a collection of single molecule work on the i-motif structure formed by the human telomeric sequence. Even though it was largely ignored in earlier years of its discovery due to its modest stability and requirement for low pH levels (pH<6.5), the i-motif has been attracting more attention recently as both a physiologically relevant structure and as a potent pH sensor. In this manuscript, we establish single molecule Förster resonance energy transfer (smFRET) as a tool to study the i-motif over a broad pH and ionic conditions. We demonstrate pH and salt dependence of i-motif formation under steady state conditions and illustrate the intermediate states visited during i-motif folding in real time at the single molecule level. We also show the prominence of intermediate folding states and reversible folding/unfolding transitions. We present an example of using the i-motif as an in-situ pH sensor and use this sensor to establish the time scale for the pH drop in a commonly used oxygen scavenging system.